Instructional Practices of Science Teachers in Directorate of Marka in the Capital Amman and their relationship with Sex & Experience and their Interaction - Baker, Hadeel Mustafa (Journal of Educational and Psychological Sciences, 2020)
The aim of this study was to determine the science teachers’ practices and the effect of sex and experience and the interaction of sex and experience. The descriptive approach was used, and a (19) Likert item scale distributed on the four domains was applied on the sample of (62) male and female. The results revealed that the assessment of general teachers’ practices was (always). The level of practices of four domains were: classroom management (always), while educational executive performance, assessment, and preparing and planning were (usually). the results showed that there were significant differences of teachers’ practices due to teachers’ experience for longer experience, and there were no statistically significant differences due to the sex and the interaction of sex and experience, The study recommended the following issues: apply results of the study in educational supervision and in teachers’ training programs, pay attention to teachers’ practices issues, and organize teaching of science in the basic cycle.